1991
DOI: 10.1017/s0021859600067071
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of lentil harvest systems for different sowing methods and cultivars in Syria

Abstract: S U M M A R YHand harvesting is a major constraint to lentil production in North Africa and West Asia. This study, in north Syria, compared hand harvesting, cutting by mower (double-knife) and cutting with angled blades on two lentil cultivars differing in standing ability and using two sowing methods (broadcast and drilled) both with and without the use of a heavy bar for field levelling in the 1984/85 season. Seven treatments were selected for testing in five locations in the 1985/86 season; and in the 1986/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

1993
1993
2023
2023

Publication Types

Select...
4
4
1

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 1 publication
0
5
1
Order By: Relevance
“…Season 1986-87 1987-88 1986-87 1987-88 1986-87 1987- Harvest losses due to the use of mechanical rather than hand harvesting increased with increasing soil moisture levels (Table 3), but plant population had no significant effect on harvest losses. Losses from the mechanical harvest of lodged crops were relatively small compared with those observed in farmers' fields and previous results of harvesting with a cutter bar (Erskine et al, 1991), possibly because the seedbed in our experimental area was more uniformly levelled than farmers' fields. The genotype X treatment interactions were not significant.…”
Section: Shoot Weightcontrasting
confidence: 55%
See 1 more Smart Citation
“…Season 1986-87 1987-88 1986-87 1987-88 1986-87 1987- Harvest losses due to the use of mechanical rather than hand harvesting increased with increasing soil moisture levels (Table 3), but plant population had no significant effect on harvest losses. Losses from the mechanical harvest of lodged crops were relatively small compared with those observed in farmers' fields and previous results of harvesting with a cutter bar (Erskine et al, 1991), possibly because the seedbed in our experimental area was more uniformly levelled than farmers' fields. The genotype X treatment interactions were not significant.…”
Section: Shoot Weightcontrasting
confidence: 55%
“…al., 1991). Genotypes with good resistance to lodging are desirable for these systems because lodging results in yield losses if it occurs early in the development of the crop (Penaloza and Mera, 1988) or if a lodged crop is mechanically harvested (Erskine et al, 1991). Lentil genotypes vary in their resistance to lodging, those with thick stems generally being most resistant (Erskine and Goodrich, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…Such cultivars include Idlib-2, Idlib-3 and Idlib-4 in Syria, Hala and Rachayya in Lebanon, IPA-98 in Iraq, Saliana and Kef in Tunisia, and Firat-87 and Sayran-96 in Turkey. On-farm trials and demonstrations have verified the value of the mechanization package (Erskine et al 1991). On average, mechanical harvesting combined with improved cultivars having good standing ability reduces harvest costs by 17-20 % (ICARDA 2001).…”
Section: Construction Of Suitable Plant Type For Mechanical Harvestmentioning
confidence: 99%
“…It is increasingly uneconomic for farmers in West Asia and North Africa to harvest the crop by hand due to the rising cost of labor and research has identified optimum systems for mechanical harvest of the crop (Snobar et al ., 1985 ;Erskine et al ., 1991) . Genotypes with a high degree of standing ability are desirable in these systems because lodging results in yield losses if it occurs early in the development of the crop (Penaloza & Mera, 1988) or if a lodged crop is machine harvested .…”
Section: Lodgingmentioning
confidence: 99%